Pendampingan dalam Pemanfaatan Content Marketing Guna Meningkatkan Kesadaran Masyarakat tentang Manfaat Hygiene Sanitasi dan Bahaya Dislipidemia - Fitriani R. Blongkod; Sudarsono; Vira Yuniar J. Paute (Journal of Hulonthalo Service Society (JHSS), 2022)
The implementation of mentoring health cadres in the use of content marketing to increase public awareness about the benefits of sanitation and the dangers of dyslipidemia in Linawan Village, Pinolosian District, South Bolaang Mongondow Regency, North Sulawesi aims to optimize the performance of health cadres in providing health services to communities outside the posyandu. The method used in providing assistance to health cadres in Linawan Village is a bottom-up method with a socio-transformative mentoring approach that places health cadres and the community as subjects who need to be given motivation, opportunities and knowledge as well as skills in planning and developing their potential. The results of the implementation of mentoring activities that have been carried out for two months show that there is a significant change in mindset and attitude patterns from the community regarding: 1) the dangers of secondary dyslipidemia caused by an unhealthy lifestyle and habits that can increase the risk of dyslipidemia such as rarely exercising, frequent consuming alcohol, smoking, and frequent consumption of sugar or saturated fat foods in the form of high-fat meats, cheese, fried foods and butter; 2) the importance of an effort made to protect, maintain and improve the health status by maintaining the cleanliness of the subject; 3) health efforts by maintaining and protecting the cleanliness of the environment of the subject.